K'uei Hsing A Repository of Asian Literature in Translation (Indiana University Press, 1974)
This appealing volume will introduce Western readers to the remarkable diversity and complexity, as well as the rich humanity, of Eastern literary traditions. A wide variety of ancient and modern literary forms is represented: poetry, short story, essay, folk song, and Jataka tale. A majority of the selections are translations from the Chinese, but Japanese, Tibetan, and Mongolian literature is also represented. Each selection is prefaced by a concise but informative introduction giving the pertinent critical and historical background.